A Phenomenological Study of Lab-Scale Tidal Turbine Loading under Combined Irregular Wave and Shear Flow Conditions - Matthew Allmark; Rodrigo Martinez; Stephanie Ordonez-Sanchez; Catherine Lloyd; Tim O’Doherty; Grégory Germain; Benoît Gaurier; Cameron Johnstone (Journal of Marine Science and Engineering, 2021)
Tidal devices are likely to faced with shear flows and subjected to various wave climates. The paper presents an experimental study of the combined impacts of shear profile and irregular waves on the loading of a 1/20th scale device operating at peak power extraction. The experiments presented were conducted at various depths to facilitate analysis of the effects of the shear flow and wave impact on the device at various positions in the water column. The fluid field was measured at three different upstream positions and at three depths (top, middle and bottom of the rotor) for each experiment; in doing so, data from the device were captured three times. The fluid measurements were of a high quality and were analysed to present the structure flow upstream of the device, which contained velocity and turbulence profiles. The upstream measurement was utilised to understand the development of flow structures in the approach to the device, and the impact of the flow structures measured was confirmed via cross-covariance calculations. The long datasets gathered were used to produce full rotational probability density functions for the blade-root-bending moments for three blades. The spectral characteristics were also considered, and showed that rotor loading quantities are less reactive to smaller scale flow structures.

Energy Yield Assessment from Ocean Currents in the Insular Shelf of Cozumel Island - Juan Carlos Alcérreca-Huerta; Job Immanuel Encarnacion; Stephanie Ordoñez-Sánchez; Mariana Callejas-Jiménez; Gabriel Gallegos Diez Barroso; Matthew Allmark; Ismael Mariño-Tapia; Rodolfo Silva Casarín; Tim O’Doherty; Cameron Johnstone; Laura Carrillo (Journal of Marine Science and Engineering, 2019)
Marine renewables represent a promising and innovative alternative source for satisfying the energy demands of growing populations while reducing the consumption of fossil fuels. Most technological advancements and energy yield assessments have focused on promoting the use of kinetic energy from tidal streams with flow velocities higher than 2.0 m s−1. However, slower-moving flows from ocean currents are recently explored due to their nearly continuous and unidirectional seasonal flows. In this study, the potential of the Yucatan Current was analysed at nearshore sites over the insular shelf of Cozumel Island in the Mexican Caribbean. Field measurements were undertaken using a vessel-mounted Acoustic Doppler Current Profiler (ADCP) to analyse the spatial distribution of flow velocities, along with Conductivity-temperature-depth (CTD) profiles as well as data gathering of bathymetry and water elevations. Northward directed flow velocities were identified, with increasing velocities just before the end of the strait of the Cozumel Channel, where average velocities in the region of 0.88–1.04 m s−1 were recorded. An estimation of power delivery using horizontal axis turbines was undertaken with Blade Element Momentum theory. It was estimated that nearly 3.2 MW could be supplied to Cozumel Island, amounting to about 10% of its electricity consumption.